2017
DOI: 10.21767/2049-5471.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Perspectives of Continuity of Care among Free Clinic Patients in the USA: A Qualitative Study

Abstract: What is known about this topic?Free clinics provide free or reduced fee health care services to un-or under-insured individuals in the United States. Continuity of care can increase amount of preventive care and diabetes care and reduce hospitalization. In general, free clinic patients are highly satisfied with care provided at free clinics. What the paper adds?Continuity of care should not only encompass seeing the same doctor over time, but also seeing well-coordinated providers. Cultural competence training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…However, ensuring continuity of care can be very challenging in a free clinic setting, because providers of free clinics are often volunteers (7,10). Patients often do not expect volunteer providers to be with the clinic for long, and do not always believe continuity of care is beneficial (11). Free clinic patients feel that they may not be able to see a provider in a timely manner if they see the same provider every visit because volunteer providers do not necessarily see patients regularly (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ensuring continuity of care can be very challenging in a free clinic setting, because providers of free clinics are often volunteers (7,10). Patients often do not expect volunteer providers to be with the clinic for long, and do not always believe continuity of care is beneficial (11). Free clinic patients feel that they may not be able to see a provider in a timely manner if they see the same provider every visit because volunteer providers do not necessarily see patients regularly (11).…”
Section: Introductionmentioning
confidence: 99%
“…Patients often do not expect volunteer providers to be with the clinic for long, and do not always believe continuity of care is beneficial (11). Free clinic patients feel that they may not be able to see a provider in a timely manner if they see the same provider every visit because volunteer providers do not necessarily see patients regularly (11). Continuity of care can be very important for patient satisfaction among free clinic patients because interpersonal communications with health-care providers influences care and outcomes (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…While the continuity of care has been identified as important for patient satisfaction because of its association with communication and coordination, a previous study has found that it is not always necessarily perceived to be a positive element for patients [8,[20][21][22]. In contrast, this study found that when respondents mentioned continuity of care in terms of a continuous relationship between a provider and a patient, it was discussed as a necessary feature in their satisfaction of their care.…”
Section: Discussionmentioning
confidence: 60%
“…Existing research concludes that patients served by a free healthcare clinic are generally satisfied, but would experience higher satisfaction with the opportunity for increased awareness of programs and services that free clinics offer [12]. However, there are few qualitative studies on patient experience and satisfaction at free clinics and of those that do exist, most have been administered through focus groups [13,14]. It is important to capture voices of free clinic patients in a written, anonymous questionnaire format, as this manner may provide more insights.…”
Section: Introductionmentioning
confidence: 99%
“…Communication is an important component of the patient–provider relationship. For example, it is possible that there are increased miscommunications between uninsured patients and providers ( 2 ). Better patient–provider relationships improve health and quality of care.…”
Section: Introductionmentioning
confidence: 99%